EFFICACY OF INTRAVENOUS IMMUNOGLOBULINS IN COMPLEX TREATMENT OF PERINATAL INFECTIONS IN PRETERM NEONATES - V.A. Bushtyriev; N.B. Laura; N.L. Nazarova ("Paediatrician" Publishers LLC, 2006)
The report provides the assessment of preterm neonates with perinatal infections (intrauterine and nosocomial) with concomitant cerebral hypoxiaaischemia and respiratory disorders and their humoral immune status. The adding of intravenous immunoglobulins to the complex treatment of perinantal infections in preterm neonates has led to significant decrease of mortality rate and shortened the time spent in resuscitation and intensive care department. intravenous immunoglobulins contribute to activation of humoral immunity and nonaspecific resistance factors. Key words: perinatal infection, intravenous immunoglobulin.